Unity 5 audio and visual effects - Lavieri, Edward D., Jr.; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"This course helps you push your Unity knowledge to the next level. This course explores many powerful features in Unity 5, from adding sound effects and ambient noise to light sources and shadows. See how to get started quickly with sounds and advanced rendering concepts to build solid games across many platforms."--Resource description page.
Presenter, Edward Lavieri.
Title from title screen (viewed August 14, 2017).
Date of publication from resource description page.
Keywords: Unity (Electronic resource); Computer games -- Design; Computer games -- Programming; Video games -- Design; Video games -- Programming; Electronic books